Enhancing Entrepreneurial Capacity among Students and Graduates through Dental Health Educational Media “The Denta Go Model” - Supriyana Supriyana; Rose Asni Latifah; Lanny Hapsari Winnursita; Nindita Enhar Satuti (Jurnal Abdimas, 2026)
Developing an entrepreneurial mindset from an early age is essential due to the high levels of creativity, innovation, and energy typically possessed by young individuals. However, entrepreneurial skills and motivation among dental health students and graduate alumni at Poltekkes Kemenkes Semarang remain limited due to inadequate mentorship and training. This community service program aimed to enhance entrepreneurial motivation and to strengthen knowledge and practical skills in developing dental health education media through the Denta Go model. The program was conducted on 13 August 2025 at the Graduate Building of Poltekkes Kemenkes Semarang and involved 20 participants, consisting of 10 dental health students and 10 graduate alumni. The intervention included entrepreneurship education, training on the development of Denta Go educational media, and hands-on simulation of the game. The results demonstrated increased participant motivation toward entrepreneurship, along with improved knowledge and skills in producing and implementing Denta Go media. The Denta Go model was perceived as easy to produce, attractive, and commercially viable, while also serving as an effective educational tool applicable in community settings. This program indicates that integrating entrepreneurship training with innovative dental health education media can support both skill development and entrepreneurial engagement among health students and graduates.